Analysing the effect of substrate properties on building envelope thermal performance in various climates - Zingre, Kishor T. (2021)
Existing regulations on the thermal efficiency of building envelope assemblies are based on the steady state thermal properties of substrate materials. Heat transfer mechanisms of passive heat curbing methods such as phase change materials and cool materials, which are dynamic in nature, are currently not being accounted for. The effectiveness of thermo-physical and solar radiation properties of building materials (i.e., solid homogeneous layers without air gap) in reducing the heat gain into a building in a hot climate could be well understood with the equivalent thermal resistance (Req) concept. A simple and easy-to-use mathematical derivation (i.e., to estimate the instantaneous heat flux across an envelope assembly) is proposed in this paper to understand the mechanism of equivalent R-value (i.e., reciprocal of thermal transmittance, U-value) due to solar radiation properties of passive substrate materials. The model is validated against field experiments carried out at two apartment units of a residential building. The Req due to high outer surface solar radiation properties (i.e., by applying a cool coating) is dynamic as it varies with the weather conditions. The effect of a substrate material’s solar radiation and thermo-physical properties on the overall roof thermal performance is investigated using the Req model for four cooling dominated climates around the globe, having different diurnal conditions and sky temperatures. Increasing the outer surface’s solar reflectance (from 10% to 80%) reduces net heat gain through the flat roof during both daytime and nighttime. In contrast, adding only thermal resistance (from 5 mm to 75 mm thick polyurethane) or volumetric heat capacity (by adding 5 mm thick phase change material) to the building envelope brings down heat gain during the day, but not in the night. Thermal insulation is found to be the second effective property, followed by thermal mass irrespective of different diurnal conditions and sky temperatures across the climates.